Barriers, support, and resilience of prospective first‐in‐family university students: Australian high school educators' perspective. Issue 7 (10th March 2022) - Pires, Charmian M.; Chapin, Laurie A.
Abstract: First‐in‐family (FiF) university students—or first generation students—are recognised to have disadvantages and lack social and cultural capital compared with non‐FiF students. The challenges FiF students encounter at university are well understood, however, their journey begins while still in high school. We call this high school cohort prospective FiF (PFiF) students and young people whose parents never attended university. This qualitative study explored the perspectives of 10 high school educators from Melbourne, Australia about the barriers and supports PFiF students encounter as they navigate the path to university. Participants identified that family inexperience, unsupportive attitudes at home and at school, lack of financial capacity and invisibility represented barriers. However, participants also explained that PFiF students can be resilient and motivated, especially when combined with appropriate support from schools, family, and university programmes. The findings highlight the challenges for PFiF and bring much‐needed attention to their challenges and needs in the early transition to higher education.